Pengaruh Kepemilikan Institusional, Komisaris Independen, Kompensasi Eksekutif, dan Kualitas Audit terhadap Penghindaran Pajak - Angellita, Putri; Sari, Dian Puji Puspita; Rodiah, Siti (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of institutional ownership, independent commissioners, executive compensation, and audit quality on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The sample was selected using a purposive sampling method with the following criteria: (1) companies listed consecutively during 2021–2023, (2) publishing annual financial reports, and (3) reports presented in Rupiah. A total of 60 companies were sampled. Data were analyzed using multiple linear regression with SPSS. The results show that all four variables—institutional ownership, independent commissioners, executive compensation, and audit quality—have a significant effect on tax avoidance. Theoretical implications support agency theory, which suggests that governance mechanisms do not always suppress opportunistic behavior but can be leveraged for tax efficiency. Practically, management needs to manage tax strategies ethically, investors need to pay attention to tax risks, and regulators are advised to tighten oversight and close legal loopholes exploited in tax avoidance practices.